Mixed Domains Enhance Charge Generation and Extraction in Bulk‐Heterojunction Solar Cells with Small‐Molecule Donors. Issue 19 (24th March 2018) - Alqahtani, Obaid; Babics, Maxime; Gorenflot, Julien; Savikhin, Victoria; Ferron, Thomas; Balawi, Ahmed H.; Paulke, Andreas; Kan, Zhipeng; Pope, Michael; Clulow, Andrew J.; Wolf, Jannic; Burn, Paul L.; et al.
Abstract: The interplay between nanomorphology and efficiency of polymer‐fullerene bulk‐heterojunction (BHJ) solar cells has been the subject of intense research, but the generality of these concepts for small‐molecule (SM) BHJs remains unclear. Here, the relation between performance; charge generation, recombination, and extraction dynamics; and nanomorphology achievable with two SM donors benzo[1, 2‐ b :4, 5‐ b ]dithiophene‐pyrido[3, 4‐ b ]‐pyrazine BDT(PPTh2 )2, namely SM1 and SM2, differing by their side‐chains, are examined as a function of solution additive composition. The results show that the additive 1, 8‐diiodooctane acts as a plasticizer in the blends, increases domain size, and promotes ordering/crystallinity. Surprisingly, the system with high domain purity (SM1) exhibits both poor exciton harvesting and severe charge trapping, alleviated only slightly with increased crystallinity. In contrast, the system consisting of mixed domains and lower crystallinity (SM2) shows both excellent exciton harvesting and low charge recombination losses. Importantly, the onset of large, pure crystallites in the latter (SM2) system reduces efficiency, pointing to possible differences in the ideal morphologies for SM‐based BHJ solar cells compared with polymer‐fullerene devices. In polymer‐based systems, tie chains between pure polymer crystals establish a continuous charge transport network, whereas SM‐based active layers may in some cases require mixed domains that enable both aggregation and charge percolation to the electrodes. Abstract : Mixed domains play a critical role in bulk heterojunction solar cells with small‐molecule (SM) donors and fullerene acceptors because of their effect on charge generation and percolation. Pure phases, important for polymer‐fullerene solar cells, are not required for the aggregation of SM donors and even hinder charge transport between domains. Increasing overall miscibility between SM donor and acceptor effectively promotes solar cell performance.